The Effect of Work Discipline, Work Motivation and Training on Employee Performance at PT Dua Delapan Ayoda Group - Iswandry Elkana Immanuel. S; Melinda Malau; Lumbantoruan , Rutman (Universitas Kristen Indonesia, 2023)
This study aims to determine the effect of work discipline, work motivation and job training on employee performance at PT Dua Eight Ayoda. The type of research used is quantitative. The object of this research is Work Discipline, Work Motivation, Job Training, and Employee Performance. The population is 50 people, then the entire population will be sampled as many as 50 employees at PT Dua Eight Ayoda. The analytical method used is validity test, reliability test, simple linear regression test, multiple linear regression, coefficient of determination hypothesis test, T test and F test. Data collection techniques used are questionnaires, interviews and literature study. The data analysis technique in this study uses regression testing and model testing (Coefficient of determination R square) and SPSS 25. The results of this study are high work discipline can improve employee performance at PT Dua Eight Ayoda, it can be concluded that there is a significant influence between work discipline high can improve employee performance indicated by a significant value <0.05; df = n-3 = 50-2 = 48, then Ha is accepted. High motivation can improve employee performance at PT Dua Eight Ayoda, so there is a significant effect between work motivation on employee performance at PT Dua Eight Ayoda, indicated by a significant value <0.05; df = n-3 = 50-2 = 48, then Ha is accepted. Optimal Job Training can improve Employee Performance at PT Dua Eight Ayoda, then there is a significant effect between Job Training on Employee Performance at PT Dua Eight Ayoda indicated by a significant value <0.05; df = n-2 = 50-2 = 48, then Ha is accepted and there is a significant overall effect between Work Discipline, Work Motivation and Job Training on Employee Performance at PT Dua Eight Ayoda. This is indicated by a significant value <5% (0.05), and df: (n-k-1) = 50-3-1 = 46, then H0 is rejected and Ha is accepted. Keywords: Work Stress, Work Motivation, Employee Performance